Synthesis, Characterization, and Biological Activity of a Novel SA-g-p(AAc-co-AM)/ZnO NP Hydrogel Composite - Aseel M. Aljeboree; Hadeel K. Albdairi; Mohammed Abed Jawad; Sarah A. Hamood; Firas H. Abdulrazzak; Ayad F. Alkaim (Engineering Proceedings)
This research investigated the preparation and efficacy of a SA-g-p(AAc-co-AM)/ZnO hydrogel composite with enhanced biological activity. The hydrogel was synthesized using the sodium alginate biopolymer through the co-polymerization method. Our findings indicate that introducing zinc oxide nanoparticles to the hydrogel amplified its biological activity. The disc diffusion technique was applied to evaluate the antimicrobial properties against two Gram-positive bacteria isolates (Staphylococcus aureus, Streptococcus epigenetics) and two Gram-negative bacteria (E.coli, Klebsiella spp.). The antimicrobial activities of three surfaces—ZnO, SA-g-p(AAc-co-AM) hydrogel, and SA-g-p(AAc-co-AM)/ZnO hydrogel composite—were assessed. Characterization of these prepared surfaces was executed using FE-SEM and EDX. The results highlighted that the ZnO NPs exhibited minimal antibacterial activity against both types of bacteria. Conversely, the SA-g-p(AAc-co-AM)/ZnO hydrogel composite demonstrated heightened antibacterial effects against Staphylococcus aureus (30 mm) and Streptococcus epigenetics (25 mm). The Gram-negative bacteria, E.coli and Klebsiella spp., recorded inhibition zones of 13 mm and 12 mm, respectively. The SA-g-p(AAc-co-AM) hydrogel showed diminished antibacterial activity relative to the composite, attributed to the absence of zinc oxide. Overall, the isolated effect of zinc oxide nanoparticles indicated a minimal antibacterial influence on all Gram-positive and Gram-negative bacteria strains.